Effect of Adding Cassava Peel and Lactic Acid Bacteria as a Feed Additive to the Weight of Immune Organs of Super Native Chicken - P. Ardiansyah; E. Suprijatna; S. Kismiati (Universitas Bengkulu, 2021)
This study aims to evaluate the use of cassava peels added with lactic acid bacteria on the immune organ weight of super native chickens. The material used in this study was 144 Day Old Chick (DOC) super unsex native chicken with an average body weight of 34 ± 3,14 gram. The research design used was a completely randomized design (CRD) with a dose of liquid feed additive in the form of a combination of cassava peel flour and lactic acid bacteria mixed with rations. The treatments in this study included T0: basal ration, T1 (basal ration + 10% feed additive ml/kg), T2 (basal ration + 15% feed additive ml/kg) and T3 (basal ration + 20% feed additive ml/kg). The parameters observed were body weight, the relative weight of lymph, thymus, and bursa Fabricius superficial chicken stock exchange. The result showed that the combination of cassava peel and lactic acid bacteria had no significant effect (P>0.05) on body weight, the relative weight of the lymph organs, thymus, and bursa Fabricius of super native chickens. This research concludes that the combination of cassava peel and lactic acid bacteria as a feed additive can maintain chickens' health by not increasing the relative weight of the super native chicken immune organs to the level of 200 ml/kg.